Dissociation of virtual photons in events with a leading proton at HERA - Chekanov, S; Derrick, M; Loizides, J; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Pavel, N; Antonioli, P; Bari, G; et al. (2004)
The ZEUS detector has been used to study dissociation of virtual photons in events with a leading proton, γ*p → Xp, in e+p collisions at HERA. The data cover photon virtualities in two ranges, 0.03 < Q2 < 0.60 GeV2 and 2 < Q2 < 100 GeV2, with MX > 1.5 GeV, where MX is the mass of the hadronic final state, X. Events were required to have a leading proton, detected in the ZEUS leading proton spectrometer, carrying at least 90% of the incoming proton energy. The cross section is presented as a function of t, the squared four-momentum transfer at the proton vertex, Φ, the azimuthal angle between the positron scattering plane and the proton scattering plane, and Q2. The data are presented in terms of the diffractive structure function, F2D(3). A next-to-leading-order QCD fit to the higher-Q2 data set and to previously published diffractive charm production data is presented. © Springer-Verlag/Società Italiana di Fisica 2004.